Respostas

2014-04-01T22:40:20-03:00
A)
( x - 1 ) ² - ( x + 1 ) ² = 0
( x - 1 ) . ( x - 1 ) - ( x + 1 ) . ( x + 1 ) = 0
( x ² - x - x + 1 ) - ( x ² + x + x + 1 ) = 0
( x ² - 2x + 1) - ( x ² + 2x + 1 ) = 0
x ² - 2x + 1 - x ² - 2x - 1 = 0
- 4x = 0
x = 0

B)
4x ² - ( 2x + 1/2 ) ² = 0
4x ² - ( 2x + 1/2 ) . ( 2x + 1/2 ) = 0
4x ² - ( 4x ² + x + x + 1 ) = 0
4x ² - ( 4x ² + 2x + 1 ) = 0
4x ² - 4x ² - 2x - 1 = 0
- 2x - 1 = 0
- 2x = 1
x = - 1/2

C)
( x + 1 ) ( x - 1 ) + 4x + 5 = 0
( x ² - x + x - 1 ) + 4x + 5 = 0
( x ² - 1 ) + 4x + 5 = 0
x ² - 1 + 4x + 5 = 0
x ² + 4x + 4 = 0

Agora resolvendo por bhaskara

a = 1; b = 4; c = 4

Δ = b² - 4 . a . c
Δ = 4² - 4 . 1 . 4
Δ = 16 - 16
Δ = 0

Como Δ = 0, essa equação não tem raizes reais, ficando com a solução vazia:

S = { }

D)
( 2x - 1 ) ( 2x + 3 ) = 0
( 4x² + 6x - 2x - 3 ) = 0
4x² + 4x - 3 = 0

Agora resolvendo por bhaskara

a = 4; b = 4; c = -3

Δ = b² - 4 . a . c
Δ = 4² - 4 . 4 . ( -3 )
Δ = 16 + 48
Δ = 64

x1 = - b + √Δ / 2 . a
x2 = - b - √Δ / 2 . a

x1 = - 4 + √64 / 2 . 4
x1 = - 4 + 8 / 2 . 4
x1 =  4 / 8
x1 = 1 / 2

x2 = - 4 - 8 / 2 . 4
x2 = - 12 / 8
x2 = - 3 / 2

S = { - 3 / 2 ; 1 / 2 }
1 5 1